2003
DOI: 10.1002/uog.905
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional cardiac abnormalities identified prior to 16 weeks' gestation in fetuses with increased nuchal translucency

Abstract: Objective To determine the accuracy and practicality of fetal echocardiography in the identification of structural and functional cardiac abnormalities prior to 16 weeks' gestation in fetuses with increased nuchal translucency thickness (NT). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 23 publications
3
45
0
2
Order By: Relevance
“…However, this corroborates the findings of studies that assessed increased NT in fetuses with normal kar yotype and found variability in the association with structural malformations, chiefly hear t defects, ranging from 4.8 to 32.1%. 8,10,11,18,19, In the present study, the chances of major structural malformation, detected in the prenatal period, also grew as NT increased, and therefore propor tions were close to the ones described by other authors.1,6,7 Nonetheless, as we observed, most malformations (78.6%) were detected in the first or second trimester. Malformations that were not diagnosed in the prenatal evaluation (unilateral, bilateral clubfoot and microtia) were isolated cases and were not associated with delayed brain development.…”
Section: Discussionsupporting
confidence: 90%
“…However, this corroborates the findings of studies that assessed increased NT in fetuses with normal kar yotype and found variability in the association with structural malformations, chiefly hear t defects, ranging from 4.8 to 32.1%. 8,10,11,18,19, In the present study, the chances of major structural malformation, detected in the prenatal period, also grew as NT increased, and therefore propor tions were close to the ones described by other authors.1,6,7 Nonetheless, as we observed, most malformations (78.6%) were detected in the first or second trimester. Malformations that were not diagnosed in the prenatal evaluation (unilateral, bilateral clubfoot and microtia) were isolated cases and were not associated with delayed brain development.…”
Section: Discussionsupporting
confidence: 90%
“…41 In this study, fifty-five pregnant women underwent specialized fetal echocardiography and 33 (60%) showed changes in heart morphology and/or function. The most common cardiac anomaly was VSD, which corresponded to 39% of abnormal diagnoses, similar to the study by Lopes et al, 57 in 2003, in which they report that out of 275 fetuses with increased NT, 24 (8.7%) had abnormal karyotype and cardiac structural abnormalities, the most frequent being the VSD, present in 38% (9 of 24). In this study, fetuses with trisomy 13/18 had a significantly higher incidence of cardiac anomalies: 60 versus 25% (T21) and 29% (45X).…”
Section: Discussionsupporting
confidence: 86%
“…11 Fetal echocardiography performed through the transvaginal route allowed adequate images of the AV septal defect in 3 patients and the hypoplastic right ventricle in 1 patient. It was also possible to diagnose 2:1 AV block in a 10-week-old fetus by using wall motion by M-mode and superior vena cava/aortic flow by Doppler imaging.…”
Section: Discussionmentioning
confidence: 99%